Small bowel intussusception and Enterobius vermicularis infestation in a 20-year-old woman. Issue 1 (19th January 2021) - Pryma, Collin; Youssef, David; Evans, David; Yang, Hui-Min
Abstract : A 20-year-old woman presented with abdominal pain and MRI findings of intussusception of the distal small bowel with no identifiable lead point and no visualisation of the appendix. A diagnostic laparoscopy succeeded in manually reducing the intussusception but was unable to find any candidate lead point. Intraoperatively, hyperperistalsis was observed throughout the small bowel which seemed prone to transient intussusception. Incidental appendectomy revealed an uninflamed appendix with Enterobius vermicularis (pinworm) infestation, the most common parasite present in appendectomy specimens worldwide. Although intussusception in young adults is an uncommon occurrence, the unique nature of this case is amplified by the concurrent finding of E. vermicularis infection of the appendix in an adolescent in western Canada, a phenomenon normally observed in paediatric populations with higher incidence in tropical areas. Although the mechanism of intussusception in this patient remains unclear, it is hypothesised that E. vermicularis colonisation acted as an irritant stimulating intestinal hypercontractility with resulting intussusception. Successful medical eradication of the pinworm in this individual may prevent future recurrence.